Balancing skilled with unskilled migration in an urbanizing agricultural economy - Nguyen, Thinh T.; Saito, H.; Isoda, H.; Ito, S. (Elsevier, 2015)
In the early stages of economic development, the migration of unskilled workers contributes to labor-intensive manufacturing production. In middle-income countries, however, the migration of skilled workers becomes the more important factor in economic progress. Evaluating the skill content of migration patterns therefore is essential to understanding migration’s economic implications. For this purpose, we investigate the determinants of skilled and unskilled migration decisions in Vietnam. Rural higher education is shown to promote knowledge-intensive production by encouraging skilled individuals to migrate to cities. In complementary fashion, commercial farm development helps alleviate urban overcrowding by encouraging unskilled individuals to remain at home.